Pemberdayaan UMKM melalui Legalitas Usaha di Desa Sukamulya Kecamatan Langkaplancar Kabupaten Pangandaran - Neneng Nurmalasari; Afi Nur Zakiyyah; Acep Rifki Padillah; Rohiman Rohiman; Yayat Hidayat (Prima Abdika: Jurnal Pengabdian Masyarakat, 2023)
In recent times the government has continued to try to expand in UMKMs, because UMKMs are one of the pillars of the economy in Indonesia. For this to be achieved, legality is needed to support the sustainability of MSMEs. The legality of UMKMs will make owners feel safe running a business without worrying that their business will be deemed illegal and closed by the government. In addition, UMKMs are also a pillar of the community and regional economy. One of them is that economic development in Indonesia has been carried out by the people of Sukamulya Village through 3 community groups in the village which are engaged in UMKM, namely, groups of mothers engaged in catering, groups of young people engaged in handicrafts made from coconut shells and community groups engaged in in the coffee sector. In doing business, of course, legality is needed to show that the business really exists. One of them is that currently the central government and regional governments require business owners to have a Business Identification Number or NIB. Business Identification Number is a business actor's identity issued by the government through the website of the OSS institution after the entrepreneur is registered. This NIB is used by business actors to obtain a business license and/or business identity and fulfill the requirements for a business license to operate. The mentoring method implemented by the author (1) Survey, (2) Interview, and (3) Focused Discussion. Assistance in making NIB was carried out in Sukamulya Village, Langkaplancar District, Pangandaran Regency. It is hoped that this NIB assistance can help MSMEs in Sukamulya Village to obtain business legality in order to facilitate the processing of other business documents, as well as to show that the business exists, operates and is viable. The target in this writing is UMKM coconut shell craftsmen in Sukamulya Village.